Nanoemulsion: process selection and application in cosmetics - a review - Yukuyama, M. N.; Ghisleni, D. D. M.; Pinto, T. J. A.; Bou-Chacra, N. A. (International journal of cosmetic science, 2016)
Synopsis In recent decades, considerable and continuous growth in consumer demand in the cosmetics field has spurred the development of sophisticated formulations, aiming at high performance, attractive appearance, sensorial benefit and safety. Yet despite increasing demand from consumers, the formulator faces certain restrictions regarding the optimum equilibrium between the active compound concentration and the formulation base taking into account the nature of the skin structure, mainly concerning to the ideal penetration of the active compound, due to the natural skin barrier. Emulsion is a mixture of two immiscible phases, and the interest in nanoscale emulsion has been growing considerably in recent decades due to its specific attributes such as high stability, attractive appearance and drug delivery properties; therefore, performance is expected to improve using a lipid‐based nanocarrier. Nanoemulsions are generated by different approaches: the so‐called high‐energy and low‐energy methods. The global overview of these mechanisms and different alternatives for each method are presented in this paper, along with their benefits and drawbacks. As a cosmetics formulation is reflected in product delivery to consumers, nanoemulsion development with prospects for large‐scale production is one of the key attributes in the method selection process. Thus, the aim of this review was to highlight the main high‐ and low‐energy methods applicable in cosmetics and dermatological product development, their specificities, recent research on these methods in the cosmetics and consideration for the process selection optimization. The specific process with regard to inorganic nanoparticles, polymer nanoparticles and nanocapsule formulation is not considered in this paper. Résumé Au cours des dernières décennies, la croissance considérable et continue de la demande des consommateurs dans le domaine des cosmétiques a stimulé le développement de formulations sophistiquées, visant à haute performance, de belle apparence, de l'avantage sensoriel et de la sécurité. Pourtant, malgré la demande croissante des consommateurs, le formulateur est confronté à certaines restrictions concernant l'équilibre optimal entre la concentration en substance active et la base de la formulation, en tenant compte de la nature de la structure de la peau, concernant principalement à la pénétration idéale de la substance active, en raison de la nature barrière de la peau. Une émulsion est un mélange de deux phases non miscibles, et l'intérêt en émulsion à l'échelle nanométrique a augmenté considérablement au cours des dernières décennies en raison de ses attributs spécifiques tels que grande stabilité, les propriétés d'apparence et de vectorisation d'actifs attrayantes; par conséquent, on peut attendre une amélioration des performances par l'utilisation d'un nanocarrier à base de lipides. Les nanoémulsions sont générées par différentes approches: les méthodes dites de haute énergie et de faible énergie. La vue d'ensemble de ces mécanismes et différentes alternatives pour chaque méthode sont présentés dans ce document, ainsi que leurs avantages et inconvénients. Le développement de nano‐émulsion avec des perspectives de production à grande échelle est l'un des attributs clés dans le processus de sélection de la méthode. Ainsi, le but de cet examen est de mettre en évidence les principales méthodes de haute et basse énergie applicables dans les cosmétiques et le développement de produits dermatologiques, leurs spécificités, des recherches récentes sur ces méthodes dans les cosmétiques, et de considération pour l'optimisation des processus de sélection. Le processus spécifique en ce qui concerne des nanoparticules inorganiques, des nanoparticules de polymère et de la formulation de nanocapsules n'est pas considéré dans le présent document.